NEW SILOS IN IMPROVING THE QUALITY OF EDUCATION - Eshmonov Otabek Usanovich (Bright Mind Publishing, 2025)
The article provides information on the developing prospects for improving the quality of correspondence education, new innovations, and thinks about new innovative projects. At the same time, ideas are also provided about the reforms that have been carried out and future updates.
Keywords: silos, innovative projects, regional economic organizations, quality of education, Ministry of Preschool Education.